Current Phylogeographic Structure of Anemone altaica (Ranunculaceae) on the Khamar-Daban Ridge Reflects Quaternary Climate Change in Baikal Siberia - Marina Protopopova; Polina Nelyubina; Vasiliy Pavlichenko (Quaternary)
Anemone altaica Fisch. ex C. A. Mey., a component of the tertiary boreo-nemoral vegetation complex, exhibits a disjunct distribution from European Russia to Central China. The Khamar-Daban Ridge, extending along Lake Baikal’s southern coast, has served as a refugium preserving mesophilic forest remnants in South Siberia since the Pleistocene. This study aimed to elucidate the phylogenetic relationships and historical biogeography of A. altaica within the Khamar-Daban refugium using plastid DNA markers (trnL + trnL-trnF). Phylogenetic and mismatch distribution analysis revealed polyphyly (more specifically diphyly) among A. altaica lineages, suggesting past hybridization events with related species followed by backcrossing. Estimation of isolation by distance effect, spatial autocorrelation analysis, PCoA, and AMOVA indicated a clear spatial genetic structure for A. altaica on the Khamar-Daban Ridge. The most reliable geographical model suggests that during periods of Pleistocene cooling, A. altaica persisted in at least six microrefugia within the ridge. Populations associated with these microrefugia formed western, central, and eastern genetic supergroups with limited gene flow among them. Gene flow likely occurred more easily during glaciations or early interglacials when the subalpine zone shifted closer to Lake Baikal due to the depression of the snow boundary, allowing adjacent populations to intermingle along the glacial edges and terminal moraines in mountain forest belt.